PERANCANGAN SISTEM INKUBATOR TELUR MULTIPURPOSE BERBASIS IOT DENGAN KENDALI FUZZY DAN KOMUNIKASI EDGE-MOBILE MELALUI JARINGAN LOKAL - Ilham Arif Farabi; Dzikri Maulana; Moh. Dicky Purnama; Susilawati (Jurnal Riset Multidisiplin Edukasi, 2025)
The reliance of conventional Internet of Things (IoT) systems on cloud connectivity often presents a significant barrier to the digitalization of livestock farming in areas with limited internet access. This study aims to design a multipurpose egg incubator system that operates independently using edge-mobile communication via a Local Area Network (LAN) and implements Fuzzy Logic algorithms for microclimate control. The system is constructed using an ESP32 as a client responsible for acquiring DHT22 sensor data and controlling actuators, and a Flutter-based smartphone acting as a local server and edge computing interface. Performance testing results demonstrate high system reliability with an average communication latency of 17.04 ms. The implementation of Fuzzy control proved effective in maintaining temperature stability with an operational average of 30.5°C. However, this study identified two operational limitations: first, the average humidity parameter was recorded at 80.7% (above the ideal range of 40-70%) due to the limited power capacity of the exhaust fan; second, continuous real-time data communication requires the smartphone application to remain in an active state (foreground). This research concludes that the LAN-based edge-mobile architecture is effective as a robust IoT alternative solution for remote areas, provided that mechanical actuator specifications and application state management are adjusted for optimal performance.